Deciphering Evolutionary Dynamics of WRKY I Genes in Rosaceae Species - Jiang, Lan; Chen, Yu; Bi, De; Cao, Yunpeng; Tong, Jiucui (Frontiers in Ecology and Evolution, 2021)
WRKY transcription factors participate in various regulation processes at different developmental stages in higher plants. Here, 97 WRKY I genes were identified in seven Rosaceae species. The WRKY I genes are highly enriched in some subgroups, and are selectively expanded in Chinese pear (Pyrus bretschneideri), and apple (Malus domestica). By searching for intra-species gene microsynteny, we found the majority of chromosomal segments for WRKY I-containing segments in both P. bretschneideri and M. domestica genomes, while paired segments were hardly scanned in other five genomes. Furthermore, we analyzed the environmental selection pressure of duplicated WRKY I gene pairs, which indicates that the strong purifying selection for WRKY domains may contribute to the stability of its structure and function. The expression patterns of duplication PbWRKY genes revealed that functional redundancy for some these genes derived from a common ancestry, and neo-functionalization or sub-functionalization for some of them. This study traces the evolution of WRKY I genes in Rosaceae genomes and lay the foundation for functional studies of these genes in the future. Our results also show that the rates of gene loss and gain in different Rosaceae genomes are far from equilibrium.